A new predictor of real economic activity: The S&P 500 option implied risk aversion - Sylvia Sarantopoulou-Chiourea; George Skiadopoulos (Queen Mary University of London, School of Economics and Finance, 2015)
We propose a new predictor of real economic activity (REA), namely the representative investor's implied relative risk aversion (IRRA) extracted from S&P 500 option prices. IRRA exploits the forward-looking information in option prices. It increases as risk averse investors enter the market, leading to a decrease in market risk premium thus predicting a REA improvement. In line with our hypothesis, IRRA predicts U.S. REA even when we control for well-known REA predictors. Results hold over both short and long horizons and regardless of the way we conduct inference. Moreover, IRRA forecasts REA out-of-sample over the 2008-2009 great economic recession peak.
Keywords: E44; G13; G17; 330; Option prices; Risk aversion; Risk-neutral moments; Real Economic Activity